2012
DOI: 10.5455/medscience.2012.01.8027
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Prevalence in Childhood Obesity and Assesment of Obesity Related Conditions

Abstract: Childhood obesity is an important risk factor for the development of metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Another point to be emphasized is that obesity in childhood increases the risk of loss of function in later life (7,13). Thus, it is important for the individuals with congenital diseases to organize their eating habits in order to reduce the possible disability due to loss of function in their future lives, and they should be guided to sufficient physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another point to be emphasized is that obesity in childhood increases the risk of loss of function in later life (7,13). Thus, it is important for the individuals with congenital diseases to organize their eating habits in order to reduce the possible disability due to loss of function in their future lives, and they should be guided to sufficient physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an intervention to improve both obese children and parents' weight loss seems a logical strategy to more fully engage a family in fundamental changes to lifestyle behavior [32]. In another study from Turkey, Araz et al found a 27% obesity rate in the siblings of obese children and adolescents [33]. Our family-based approach seems to motivate both the child and other family members to change eating habits.…”
mentioning
confidence: 91%
“…Obezite tedavisi başlanan hastaların psikiyatri hekimlerinin de bulunduğu bir ekip tarafından takip edilmesi hastaların diyete uyumunu artırılabilir ve komorbid psikopatolojilerin önlenmesi sağlanabilir. Anahtar kelimeler: Obez, öfke, metabolik sendrom GİRİŞ Obezite her yaşta görülebilmekle beraber, toplumda en yaygın görülen fiziksel hastalık ve halk sağlığı sorunudur 1,2 . Birleşik Amerika'da yetişkinler arasında obezite prevalansının 1990 yılında %23, 2000 yılında ise %31 olduğu belirtilmiştir 3 .…”
unclassified